Agroforestry practices and on-site charcoal production enhance soil fertility and climate change mitigation in northwestern Ethiopia - Kim, Dong-Gill; Kassahun, Gashaw; Yimer, Fantaw; Brüggemann, Nicolas; Glaser, Bruno (Agronomy for sustainable development, 2022)
In northwestern Ethiopia, a conventional teff ( Eragrostis tef (Zucc.) Trotter) monoculture was converted into a rotational agroforestry system (teff-Acacia agroforestry), which consists of the sequence i) teff- Acacia decurrens intercropping (1 st year), ii) grass- A. decurrens silvopasture (2 nd year), iii) A. decurrens plantation (3 rd –4 th year), and iv) on-site charcoal production from A. decurrens (end of 4 th year) . This study is the first one to comprehensively show how the agroforestry system affects soil organic carbon (SOC) and soil nutrients. Soil samples were collected from the teff-Acacia agroforestry and conventional teff fields at two different sites (site I and II) and they were used to determine soil pH, black carbon, SOC, soil total nitrogen (STN), extractable phosphorus (P), potassium (K), magnesium (Mg), sodium (Na), and calcium (Ca) contents. At site I (0–10 cm soil depth), charcoal production spots in teff-Acacia agroforestry had higher soil pH (20%), black carbon (164%), SOC (48%), P (687%), and K (788%) contents compared to outside charcoal production spots. Soil organic carbon and STN contents in the 1 st and 2 nd teff-Acacia agroforestry rotations were significantly higher (SOC: 112–169%, STN: 100–131%) than teff fields. At site II, SOC stocks (0–100 cm) in the 1 st agroforestry rotation were not significantly different from teff fields. However, they were 159% and 244% greater in the 2 nd and 3 rd agroforestry rotations, respectively, compared to teff fields. Conversion of teff fields to teff-Acacia agroforestry for a 12-year period increased SOC stocks by 21 Mg C ha –1 per year. Our results demonstrated that locally adopted agroforestry practices can increase SOC and nutrients in the long term, thereby contributing to enhanced soil fertility and improved climate change mitigation strategies via carbon sequestration.